A comparative MRI study of cartilage damage in gout versus rheumatoid arthritis. Issue 4 (23rd April 2015) - Popovich, Ivor; Lee, Arier CL; Doyle, Anthony; McHaffie, Alexandra; Clarke, Andrew; Reeves, Quentin; Dalbeth, Nicola; McQueen, Fiona M
Abstract: Introduction: Magnetic resonance imaging (MRI) is useful for detecting joint inflammation and damage in the inflammatory arthropathies. This study aimed to investigate MRI cartilage damage and its associations with joint inflammation in patients with gout compared with a group with rheumatoid arthritis (RA). Methods: Forty patients with gout and 38 with seropositive RA underwent 3T‐MRI of the wrist with assessment of cartilage damage at six carpal sites, using established scoring systems. Synovitis and bone oedema (BME) were graded according to Rheumatoid Arthritis MRI Scoring System criteria. Cartilage damage was compared between the groups adjusting for synovitis and disease duration using logistic regression analysis. Results: Compared with RA, there were fewer sites of cartilage damage and lower total damage scores in the gout group ( P  = 0.02 and 0.003), adjusting for their longer disease duration and lesser degree of synovitis. Cartilage damage was strongly associated with synovitis in both conditions (R = 0.59, P  < 0.0001 and R = 0.52, P  = 0.0045 respectively) and highly correlated with BME in RA (R = 0.69, P  < 0.0001) but not in gout (R = 0.095, P  = 0.56). Conclusions: Cartilage damage is less severe in gout than in RA, with fewer sites affected and lower overall scores. It is associated with synovitis in both diseases, likely indicating an effect of pro‐inflammatory cytokine production on cartilage integrity. However, the strong association between cartilage damage and BME observed in RA was not identified in gout. This emphasizes differences in the underlying pathophysiology of joint damage in these two conditions.